Ordinary Stories in Extraordinary Times: Marcie Hershman’s Tales of the Master Race - Kolář, Stanislav (American & British Studies Annual, 2020)
This paper examines the categories of perpetrators, bystanders and victims as represented among the characters of Marcie Hershman’s short story cycle Tales of the Master Race. The main focus is on the characters of perpetrators, as it is predominantly from their perspectives that Hershman depicts life in a small German town during the Third Reich. The paper aims to explore the social-psychological reasons for the perpetration of evil, be it conformity to authorities or ideological anti-Semitism. It also points to a certain fluidity in the examined categories of the characters, demonstrating the thin borders among them.